Composition for electric storage device, slurry for electric storage device electrode, electric storage device electrode, and electric storage device

JP7638872B2Active Publication Date: 2025-03-04ENEOS MATERIALS CORP
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2021539300
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-08-13
Filing Date
2020-08-11
Publication Date
2025-03-04
Estimated Expiration
2040-08-11

AI Technical Summary

Benefits of technology

【0024】 本発明に係る蓄電デバイス用組成物によれば、密着性に優れているため、良好な充放電耐久特性を示す蓄電デバイス電極を製造することができる。本発明に係る蓄電デバイス用組成物は、蓄電デバイス電極が活物質としてリチウム吸蔵量の大きい材料、例えばグラファイトのような炭素材料やケイ素材料を含有する場合に特に上記の効果を発揮する。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007638872000001
    Figure 0007638872000001
  • Figure 0007638872000002
    Figure 0007638872000002
  • Figure 0007638872000003
    Figure 0007638872000003
Patent Text Reader

Abstract

The present invention provides a composition for electricity storage devices, said composition enabling the production of an electricity storage device electrode that has good charge / discharge durability characteristics, while exhibiting excellent adhesion. A composition for electricity storage devices according to the present invention contains (A) polymer particles, (B) a polymer and (C) a liquid medium; if the total of the repeating units contained in the polymer particles (A) is taken as 100 parts by mass, the polymer particles (A) contain from 20 to 65 parts by mass of (a1) a repeating unit derived from a conjugated diene compound and from 1 to 40 parts by mass of (a2) a repeating unit derived from an α, β-unsaturated nitrile compound; and if the total of the repeating units contained in the polymer (B) is taken as 100 parts by mass, the polymer (B) contains from 5 to 95 parts by mass of (b1) a repeating unit derived from an unsaturated carboxylic acid and from 5 to 95 parts by mass of (b2) a repeating unit derived from a (meth)acrylamide.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composition for an electricity storage device, a slurry for an electricity storage device electrode containing the composition and an active material, an electricity storage device electrode formed by applying the slurry to a current collector and drying it, and an electricity storage device including the electrode. [Background technology]

[0002] In recent years, there has been a demand for power storage devices having high voltage and high energy density as power sources for driving electronic devices. Lithium ion batteries and lithium ion capacitors are expected to be such power storage devices.

[0003] Electrodes used in such electricity storage devices are usually produced by applying a composition (electrode slurry) containing an active material and a polymer that functions as a binder to the surface of a current collector and drying it. The properties required of the polymer used as a binder include the ability to bind active materials together and the ability to adhere to the current collector, abrasion resistance in the process of winding up the electrode, and resistance to powdering so that fine powder of the active material does not fall off from the applied and dried composition coating film (hereinafter also referred to as the "active material layer") even when the electrode is subsequently cut.

[0004] It has been empirically demonstrated that the binding ability between the active materials, the adhesion ability between the active material and the current collector, and the resistance to powder falling off are almost proportional to the performance, and therefore, in the present specification, these may be collectively referred to as "adhesion".

[0005] In recent years, in order to meet the demands for higher output and higher energy density of power storage devices, studies have been conducted on the use of materials with a large lithium storage capacity as active materials. For example, as disclosed in Patent Document 1, a method of utilizing a silicon material with a theoretical lithium storage capacity of up to about 4,200 mAh / g as an active material is considered promising.

[0006] However, active materials using such materials with large lithium occlusion capacity undergo large volume changes due to the absorption and release of lithium, and therefore, when conventional electrode binders are applied to such materials with large lithium occlusion capacity, the adhesiveness cannot be maintained and the active material peels off, resulting in a significant capacity loss during charging and discharging.

[0007] As techniques for improving the adhesion of electrode binders, techniques for controlling the amount of surface acid on particulate binder particles (see Patent Documents 2 and 3) and techniques for improving the above-mentioned properties by using binders having epoxy groups or hydroxyl groups (see Patent Documents 4 and 5) have been proposed. In addition, a technique for binding active materials with the rigid molecular structure of polyimide to suppress volumetric changes of the active materials has also been proposed (see Patent Document 6).

[0008] On the other hand, lithium-containing phosphate compounds having an olivine structure (hereinafter also referred to as "olivine-type lithium-containing phosphate compounds") have been attracting attention as a highly safe positive electrode active material. Olivine-type lithium-containing phosphate compounds have high thermal stability because phosphorus and oxygen are covalently bonded, and do not release oxygen even at high temperatures.

[0009] However, the output voltage of the olivine-type lithium-containing phosphate compound is low because the Li-ion absorption / release voltage is about 3.4 V. To compensate for this drawback, attempts have been made to improve the properties of peripheral materials such as electrode binders and electrolytes (see Patent Documents 7 to 9). [Prior art documents] [Patent documents]

[0010] [Patent Document 1] JP 2004-185810 A [Patent Document 2] International Publication No. 2011 / 096463 [Patent Document 3] International Publication No. 2013 / 191080 [Patent Document 4] JP 2010-205722 A [Patent Document 5] JP 2010-3703 A [Patent Document 6] JP 2011-204592 A [Patent Document 7] JP 2007-294323 A [Patent Document 8] International Publication No. 2010 / 113940 [Patent Document 9] JP 2012-216322 A Summary of the Invention [Problem to be solved by the invention]

[0011] However, the electrode binders disclosed in the above Patent Documents 1 to 6 do not have sufficient adhesion for practical use of new active materials, such as silicon materials, which have a large lithium occlusion capacity and a large volume change associated with the occlusion and release of lithium. When such electrode binders are used, the active material falls off due to repeated charging and discharging, causing the electrode to deteriorate, and there is a problem that the durability required for practical use cannot be sufficiently obtained.

[0012] In addition, the techniques for improving the properties of peripheral materials such as electrode binders and electrolytes as disclosed in the above Patent Documents 7 to 9 have made it difficult to sufficiently improve the charge-discharge durability of an electricity storage device having a positive electrode in which an olivine-type lithium-containing phosphate compound is used as a positive electrode active material.

[0013] Thus, some aspects of the present invention provide a composition for an electricity storage device capable of producing an electricity storage device electrode that has excellent adhesion and exhibits good charge / discharge durability characteristics. Some aspects of the present invention also provide a slurry for an electricity storage device electrode that contains the composition. Some aspects of the present invention also provide an electricity storage device electrode that has excellent adhesion and exhibits good charge / discharge durability characteristics. Furthermore, some aspects of the present invention provide an electricity storage device that has excellent charge / discharge durability characteristics. [Means for solving the problem]

[0014] The present invention has been made to solve at least a part of the above-mentioned problems, and can be realized in any of the following aspects.

[0015] One aspect of the composition for an electrical storage device according to the present invention is Contains polymer particles (A), a polymer (B), and a liquid medium (C), When the total amount of repeating units contained in the polymer particles (A) is 100 parts by mass, the polymer particles (A) 20 to 65 parts by mass of a repeating unit (a1) derived from a conjugated diene compound; and 1 to 40 parts by mass of a repeating unit (a2) derived from an α,β-unsaturated nitrile compound, When the total amount of repeating units contained in the polymer (B) is 100 parts by mass, the polymer (B) 5 to 95 parts by mass of a repeating unit (b1) derived from an unsaturated carboxylic acid; and 5 to 95 parts by mass of a repeating unit (b2) derived from (meth)acrylamide.

[0016] In one embodiment of the composition for an electrical storage device, When the content of the polymer particles (A) is Ma parts by mass and the content of the polymer (B) is Mb parts by mass, the value of Mb / Ma may be 0.25 to 99.

[0017] In any one of the embodiments of the composition for an electrical storage device, The number average particle size of the polymer particles (A) may be 50 nm or more and 500 nm or less.

[0018] In any one of the embodiments of the composition for an electrical storage device, The liquid medium (C) may be water.

[0019] One embodiment of a slurry for an electric storage device electrode according to the present invention is The composition for an electricity storage device according to any one of the above aspects and an active material are contained therein.

[0020] In one embodiment of the slurry for an electricity storage device electrode, The active material may contain a silicon material.

[0021] In any one of the embodiments of the slurry for an electricity storage device electrode, It may further comprise a thickening agent.

[0022] One aspect of the electricity storage device electrode according to the present invention is The electrode assembly includes a current collector and an active material layer formed by applying the slurry for an electricity storage device electrode according to any one of the above aspects onto a surface of the current collector and drying the applied active material layer.

[0023] One aspect of the electricity storage device according to the present invention is The power storage device includes the electrode according to the above aspect. Effect of the Invention

[0024] The composition for an electricity storage device according to the present invention has excellent adhesion, and therefore it is possible to produce an electricity storage device electrode that exhibits good charge / discharge durability characteristics. The composition for an electricity storage device according to the present invention exerts the above-mentioned effects particularly when the electricity storage device electrode contains a material with a large lithium occlusion capacity as an active material, for example, a carbon material such as graphite or a silicon material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] Preferred embodiments of the present invention will be described in detail below. Note that the present invention is not limited to the embodiments described below, and should be understood to include various modified examples that are implemented within the scope of the present invention.

[0026] In this specification, the term "(meth)acrylic acid" encompasses both "acrylic acid" and "methacrylic acid". Similarly, the term "(meth)acrylate" encompasses both "acrylate" and "methacrylate". Similarly, the term "(meth)acrylamide" encompasses both "acrylamide" and "methacrylamide".

[0027] In this specification, a numerical range described using "to" means that the numerical range includes the numerical values ​​before and after "to" as the lower limit and upper limit.

[0028] 1. Composition for Electricity Storage Devices The composition for an electricity storage device according to one embodiment of the present invention contains polymer particles (A), a polymer (B), and a liquid medium (C). The composition for an electricity storage device according to this embodiment can be used as a material for producing an electricity storage device electrode (active material layer) having improved bonding ability between active materials, improved adhesion ability between the active material and a current collector, and improved resistance to powder falling off, and can also be used as a material for forming a protective film for suppressing a short circuit caused by dendrites that occur during charging and discharging. Each component contained in the composition for an electricity storage device according to this embodiment will be described in detail below.

[0029] 1.1. Polymer particles (A) The polymer particles (A) contained in the electricity storage device composition according to this embodiment are in the form of a latex dispersed in a liquid medium (C). The polymer particles (A) in the form of a latex dispersed in a liquid medium (C) are preferred because they improve the stability of a slurry for an electricity storage device electrode (hereinafter simply referred to as "slurry") prepared by mixing the polymer particles (A) with an active material, and also improve the applicability of the slurry to a current collector.

[0030] The polymer particles (A) contain, when the total number of repeating units in the polymer particles (A) is 100 parts by mass, 20 to 65 parts by mass of repeating units (a1) (hereinafter also referred to as "repeating units (a1)") derived from a conjugated diene compound and 1 to 40 parts by mass of repeating units (a2) (hereinafter also referred to as "repeating units (a2)") derived from an α,β-unsaturated nitrile compound. In addition to the repeating units, the polymer particles (A) may contain repeating units derived from other monomers copolymerizable therewith.

[0031] The repeating units constituting the polymer particles (A), the physical properties of the polymer particles (A), and the synthesis method of the polymer particles (A) will be described below in that order.

[0032] 1.1.1. Repeating units constituting polymer particles (A) 1.1.1.1. Repeating units derived from conjugated diene compounds (a1) The content of the repeating unit (a1) derived from a conjugated diene compound is 20 to 65 parts by mass when the total of the repeating units contained in the polymer particles (A) is 100 parts by mass. The lower limit of the content of the repeating unit (a1) is preferably 22 parts by mass, more preferably 25 parts by mass. The upper limit of the content of the repeating unit (a1) is preferably 60 parts by mass, more preferably 55 parts by mass. When the polymer particles (A) contain the repeating unit (a1) in the above range, the dispersibility of the active material and the filler is improved, and a uniform active material layer and a protective film can be prepared, so that the structural defects of the electrode plate are eliminated and good charge and discharge characteristics are exhibited. In addition, the polymer particles (A) that cover the surface of the active material can be given elasticity, and the polymer can be stretched and stretched to improve adhesion, so that good charge and discharge durability characteristics are exhibited.

[0033] The conjugated diene compound is not particularly limited, but may be 1,3-butadiene, 2-methyl-1,3-butadiene, 2,3-dimethyl-1,3-butadiene, 2-chloro-1,3-butadiene, etc., and one or more selected from these may be used. Among these, 1,3-butadiene is particularly preferred.

[0034] 1.1.1.2. Repeating unit (a2) derived from an α,β-unsaturated nitrile compound The content of the repeating unit (a2) derived from an α,β-unsaturated nitrile compound is 1 to 40 parts by mass when the total of the repeating units contained in the polymer particle (A) is 100 parts by mass. The lower limit of the content of the repeating unit (a2) is preferably 3 parts by mass, more preferably 5 parts by mass. The upper limit of the content of the repeating unit (a2) is preferably 35 parts by mass, more preferably 30 parts by mass. By containing the repeating unit (a2) in the above range in the polymer particle (A), it is possible to reduce the dissolution of the polymer particle (A) in the electrolyte solution, and the decrease in adhesion due to the electrolyte solution can be suppressed. In addition, the increase in internal resistance caused by the polymer component dissolved in the electricity storage device becoming an electric resistance component can be suppressed.

[0035] The α,β-unsaturated nitrile compound is not particularly limited, and examples thereof include acrylonitrile, methacrylonitrile, α-chloroacrylonitrile, α-ethylacrylonitrile, vinylidene cyanide, etc., and one or more selected from these can be used. Among these, one or more selected from the group consisting of acrylonitrile and methacrylonitrile are preferred, and acrylonitrile is particularly preferred.

[0036] 1.1.1.3. Other repeating units In addition to the repeating units (a1) and (a2), the polymer particles (A) may contain repeating units derived from other monomers that are copolymerizable with the repeating units (a1) and (a2). Examples of such repeating units include repeating units (a3) ​​derived from aromatic vinyl compounds (hereinafter also simply referred to as "repeating units (a3)"); repeating units (a4) derived from unsaturated carboxylic acids (hereinafter also simply referred to as "repeating units (a4)"); repeating units (a5) derived from (meth)acrylamide (hereinafter also simply referred to as "repeating units (a5)"); repeating units (a6) derived from unsaturated carboxylic acid esters (hereinafter also simply referred to as "repeating units (a6)"); repeating units (a7) derived from compounds having sulfonic acid groups (hereinafter also simply referred to as "repeating units (a7)"); and repeating units derived from cationic monomers.

[0037] <Repeating Unit (a3) ​​Derived from an Aromatic Vinyl Compound> When the polymer particles (A) contain a repeating unit (a3) ​​derived from an aromatic vinyl compound, the content of the repeating unit (a3) ​​is preferably 0 to 50 parts by mass when the total of the repeating units contained in the polymer particles (A) is taken as 100 parts by mass. The lower limit of the content of the repeating unit (a3) ​​is preferably 3 parts by mass, more preferably 5 parts by mass. The upper limit of the content of the repeating unit (a3) ​​is preferably 40 parts by mass, more preferably 30 parts by mass. When the polymer particles (A) contain the repeating unit (a3) ​​in the above range, the polymer particles (A) have an appropriate binding force with respect to graphite used as an active material, and an electricity storage device electrode having excellent flexibility and adhesion may be obtained.

[0038] The aromatic vinyl compound is not particularly limited, and examples thereof include styrene, α-methylstyrene, p-methylstyrene, vinyltoluene, chlorostyrene, divinylbenzene, etc., and one or more selected from these can be used. Among these, one or more selected from the group consisting of styrene and divinylbenzene are preferred, and styrene is particularly preferred.

[0039] <Repeating Unit (a4) Derived from Unsaturated Carboxylic Acid> When the polymer particle (A) contains a repeating unit (a4) derived from an unsaturated carboxylic acid, the content of the repeating unit (a4) is preferably 1 to 40 parts by mass when the total of the repeating units contained in the polymer particle (A) is 100 parts by mass. The lower limit of the content of the repeating unit (a4) is preferably 3 parts by mass, more preferably 5 parts by mass. The upper limit of the content of the repeating unit (a4) is preferably 35 parts by mass, more preferably 30 parts by mass. When the polymer particle (A) contains the repeating unit (a4) in the above range, the dispersibility of the active material and the filler may be improved. Furthermore, the affinity with the silicon material as the active material may be improved, and the swelling of the silicon material may be suppressed, thereby exhibiting good charge / discharge durability characteristics.

[0040] The unsaturated carboxylic acid is not particularly limited, but may be monocarboxylic acid or dicarboxylic acid (including anhydride) such as acrylic acid, methacrylic acid, crotonic acid, maleic acid, fumaric acid, itaconic acid, etc., and one or more selected from these may be used. Among these, it is preferable to use one or more selected from acrylic acid, methacrylic acid, and itaconic acid.

[0041] <Repeating unit (a5) derived from (meth)acrylamide> When the polymer particles (A) contain a repeating unit (a5) derived from (meth)acrylamide, the content of the repeating unit (a5) is preferably 0 to 10 parts by mass when the total of the repeating units contained in the polymer particles (A) is 100 parts by mass. The lower limit of the content of the repeating unit (a5) is preferably 0.5 parts by mass, more preferably 1 part by mass. The upper limit of the content of the repeating unit (a5) is preferably 9 parts by mass, more preferably 8 parts by mass. When the polymer particles (A) contain the repeating unit (a5) in the above range, the dispersibility of the active material and the filler in the slurry may be improved. In addition, the flexibility of the obtained active material layer may become appropriate, and the adhesion between the current collector and the active material layer may be improved. Furthermore, the bonding ability between the active materials containing a carbon material such as graphite and a silicon material can be increased, so that an active material layer having better flexibility and adhesion to the current collector may be obtained.

[0042] The (meth)acrylamide is not particularly limited, but examples thereof include acrylamide, methacrylamide, N-isopropylacrylamide, N,N-dimethylacrylamide, N,N-dimethylmethacrylamide, N,N-diethylacrylamide, N,N-diethylmethacrylamide, N,N-dimethylaminopropylacrylamide, N,N-dimethylaminopropylmethacrylamide, N-methylolmethacrylamide, N-methylolacrylamide, diacetoneacrylamide, maleic acid amide, and acrylamide tert-butylsulfonic acid, and one or more selected from these can be used.

[0043] <Repeating Unit (a6) Derived from Unsaturated Carboxylic Acid Ester> When the polymer particle (A) contains a repeating unit (a6) derived from an unsaturated carboxylic acid ester, the content of the repeating unit (a6) is preferably 0 to 30 parts by mass when the total of the repeating units contained in the polymer particle (A) is 100 parts by mass. The lower limit of the content of the repeating unit (a6) is preferably 3 parts by mass, more preferably 5 parts by mass. The upper limit of the content of the repeating unit (a6) is preferably 25 parts by mass, more preferably 20 parts by mass. When the polymer particle (A) contains the repeating unit (a6) in the above range, the affinity between the polymer particle (A) and the electrolyte is improved, and an increase in internal resistance due to the binder becoming an electric resistance component in the electricity storage device is suppressed, and a decrease in adhesion due to excessive absorption of the electrolyte may be prevented.

[0044] Among the unsaturated carboxylic acid esters, (meth)acrylic acid esters can be preferably used.Specific examples of (meth)acrylic acid esters include, for example, methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, n-amyl (meth)acrylate, isoamyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, tri(meth)acrylic acid, ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate ... Examples of the acrylate include trimethylolpropane, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, allyl (meth)acrylate, 2-hydroxymethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 5-hydroxypentyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, glycerin mono(meth)acrylate, and glycerin di(meth)acrylate, and one or more selected from these can be used. Among these, one or more selected from methyl (meth)acrylate, ethyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate are preferred, and methyl (meth)acrylate is particularly preferred.

[0045] <Repeating Unit (a7) Derived from a Compound Having a Sulfonic Acid Group> When the polymer particles (A) contain a repeating unit (a7) derived from a compound having a sulfonic acid group, the content of the repeating unit (a7) is preferably 0 to 10 parts by mass when the total of the repeating units contained in the polymer particles (A) is 100 parts by mass. The lower limit of the content of the repeating unit (a7) is preferably 0.5 parts by mass, more preferably 1 part by mass. The upper limit of the content of the repeating unit (a7) is preferably 9 parts by mass, more preferably 8 parts by mass.

[0046] The compound having a sulfonic acid group is not particularly limited, but examples thereof include vinyl sulfonic acid, styrene sulfonic acid, allyl sulfonic acid, sulfoethyl (meth)acrylate, sulfopropyl (meth)acrylate, sulfobutyl (meth)acrylate, 2-acrylamido-2-methylpropanesulfonic acid, 2-hydroxy-3-acrylamidopropanesulfonic acid, 3-allyloxy-2-hydroxypropanesulfonic acid, and alkali salts thereof, and one or more selected from these may be used.

[0047] <Repeating units derived from cationic monomers> The polymer particles (A) may contain a repeating unit derived from a cationic monomer. The cationic monomer is not particularly limited, but is preferably at least one monomer selected from the group consisting of secondary amines (salts), tertiary amines (salts) and quaternary ammonium salts. Specific examples of these cationic monomers include, but are not limited to, 2-(dimethylamino)ethyl (meth)acrylate, dimethylaminoethyl (meth)acrylate methyl chloride quaternary salt, 2-(diethylamino)ethyl (meth)acrylate, 3-(dimethylamino)propyl (meth)acrylate, 3-(diethylamino)propyl (meth)acrylate, 4-(dimethylamino)phenyl (meth)acrylate, 2-[(3,5-dimethylpyrazolyl)carbonylamino]ethyl (meth)acrylate, 2-(0-[1'-methylpropylideneamino]carboxyamino)ethyl (meth)acrylate, 2-(1-aziridinyl)ethyl (meth)acrylate, methacryloylcholine chloride, and tris(2-acryloyloxyethyl) isocyanurate. ), 2-vinylpyridine, quinaldine red, 1,2-di(2-pyridyl)ethylene, 4'-hydrazino-2-stilbazole dihydrochloride hydrate, 4-(4-dimethylaminostyryl)quinoline, 1-vinylimidazole, diallylamine, diallylamine hydrochloride, triallylamine, diallyldimethylammonium chloride, dichlormid, N-allylbenzylamine, N-allylaniline, 2,4-diamino-6-diallylamino-1,3,5-triazine, N-trans-cinnamyl-N-methyl-(1-naphthylmethyl)amine hydrochloride, trans-N-(6,6-dimethyl-2-hepten-4-ynyl)-N-methyl-1-naphthylmethylamine hydrochloride, and the like can be mentioned, and one or more selected from these can be used.

[0048] 1.1.2. Physical properties of polymer particles (A) 1.1.2.1.Number average particle size The number average particle diameter of the polymer particles (A) is preferably 50 nm or more and 500 nm or less, more preferably 60 nm or more and 450 nm or less, and particularly preferably 70 nm or more and 400 nm or less. When the number average particle diameter of the polymer particles (A) is within the above range, the polymer particles (A) are easily adsorbed on the surface of the active material, so that the polymer particles (A) can move along with the movement of the active material. As a result, migration can be suppressed, and the deterioration of electrical properties can be reduced.

[0049] The number average particle size of the polymer particles (A) can be determined from the particle size distribution measured using a particle size distribution measuring device that uses dynamic light scattering as the measurement principle. For example, the particle size distribution measuring device may be the "FPAR-1000" model manufactured by Otsuka Electronics Co., Ltd.

[0050] 1.1.2.2.Viscosity When the viscosity of an aqueous dispersion of polymer particles (A) having a solid content concentration of 5% and a pH of 9 is measured at a temperature of 25° C. using a Brookfield viscometer, the viscosity is preferably 1 to 50 mPa·s / 30 rpm, more preferably 3 to 45 mPa·s / 30 rpm, and particularly preferably 5 to 40 mPa·s / 30 rpm. This viscosity can be measured in accordance with JIS Z 8803. As the Brookfield viscometer, for example, "RB-80L" or "TVB-10" manufactured by Toki Sangyo Co., Ltd. can be used.

[0051] 1.1.2.3. Weight average molecular weight (Mw) The weight average molecular weight (Mw) of the THF (tetrahydrofuran) soluble component of the polymer particles (A) is preferably 1,000 or more, more preferably 10,000 or more, and particularly preferably 100,000 or more. When the weight average molecular weight (Mw) of the polymer particles (A) is within the above range, adhesion is good, and it is easy to obtain an electricity storage device with excellent charge and discharge characteristics. Weight The average molecular weight can be measured, for example, by a GPC method under the following conditions.

[0052] 10 mg of the polymer dispersion is mixed with 5 mL of THF, left at 25°C for 16 hours, and then passed through a 0.45 μm membrane filter to obtain a measurement sample. Next, using the measurement sample obtained under the following measurement conditions, the weight average molecular weight (Mw) of the THF-soluble component is determined in terms of polystyrene (RI detection) by gel permeation chromatography using the following column. [Measurement conditions] ·Temperature: 35℃ Solvent: THF ·Flow rate: 1.0mL / min ·Concentration: 0.2% by weight Measurement sample injection volume: 100μL [column] "GPC TSKgel α-2500" (30 cm x 2 tubes) manufactured by Tosoh Corporation was used. (Log between Mw 1,000 and 20,000,000) 10 (Measured under conditions where the linear correlation between Mw and elution time is 0.98 or higher.)

[0053] 1.1.3. Method for synthesizing polymer particles (A) The method for synthesizing the polymer particles (A) is not particularly limited, but for example, it can be an emulsion polymerization method carried out in the presence of a known emulsifier (surfactant), chain transfer agent, polymerization initiator, etc. As the emulsifier (surfactant), chain transfer agent, and polymerization initiator, compounds described in Japanese Patent No. 5999399 and the like can be used.

[0054] The polymerization initiator used in the synthesis of the polymer particles (A) is preferably a water-soluble radical initiator, and particularly preferably a persulfate such as lithium persulfate, potassium persulfate, sodium persulfate, ammonium persulfate, or a water-soluble azo initiator such as 4,4'-azobis(4-cyanovaleric acid). The amount of the polymerization initiator used is preferably 0.1 to 5.0 parts by mass relative to 100 parts by mass of the total mass of the monomers used in the polymerization.

[0055] The polymerization temperature during production of the polymer particles (A) is not particularly limited, but taking into consideration the production time and the conversion rate (reaction rate) of monomers to copolymers, the synthesis is preferably performed within the range of 30 to 95° C., more preferably 50 to 85° C. In addition, during polymerization, a pH adjuster or a metal ion sequestering agent such as EDTA or a salt thereof can also be used for the purpose of improving production stability.

[0056] In addition, the pH may be adjusted before or after polymerization with a general neutralizing agent such as ammonia, organic amine, potassium hydroxide, sodium hydroxide, or lithium hydroxide, and in this case, the pH is preferably adjusted to a range of 5 to 11. It is also possible to use a metal ion-sequestering agent such as EDTA or a salt thereof.

[0057] 1.2. Polymer (B) The polymer (B) contained in the composition for an electricity storage device according to this embodiment may be in the form of a latex dispersed in the liquid medium (C) or may be dissolved in the liquid medium (C), but is preferably dissolved in the liquid medium (C). When the polymer (B) is dissolved in the liquid medium (C), the stability of the slurry produced by mixing the polymer (B) with the active material is improved, and the coating property of the slurry onto a current collector is also improved, which is preferable.

[0058] The polymer (B) contains, when the total number of repeating units in the polymer (B) is 100 parts by mass, 5 to 95 parts by mass of a repeating unit (b1) (hereinafter also referred to as "repeating unit (b1)") derived from an unsaturated carboxylic acid and 5 to 95 parts by mass of a repeating unit (b2) (hereinafter also referred to as "repeating unit (b2)") derived from (meth)acrylamide. In addition to the repeating units, the polymer (B) may contain a repeating unit derived from another monomer copolymerizable therewith.

[0059] The repeating units constituting the polymer (B), the physical properties of the polymer (B), and the synthesis method of the polymer (B) will be described below in that order.

[0060] 1.2.1. Repeating units constituting polymer (B) 1.2.1.1. Repeating units derived from unsaturated carboxylic acids (b1) The content of the repeating unit (b1) derived from the unsaturated carboxylic acid is 5 to 95 parts by mass when the total of the repeating units contained in the polymer (B) is 100 parts by mass. The lower limit of the content of the repeating unit (b1) is preferably 8 parts by mass, more preferably 10 parts by mass. The upper limit of the content of the repeating unit (b1) is preferably 90 parts by mass, more preferably 80 parts by mass. When the polymer (B) contains the repeating unit (b1) in the above range, the dispersibility of the active material and the filler is improved. The affinity with the silicon material as the active material is improved, and the swelling of the silicon material is suppressed, thereby exhibiting good charge / discharge durability characteristics.

[0061] Examples of the unsaturated carboxylic acid include the same compounds as those exemplified in the description of the repeating unit (a4) above. Among these, it is preferable to use one or more selected from acrylic acid, methacrylic acid, and itaconic acid.

[0062] 1.2.1.2. Repeating units derived from (meth)acrylamide (b2) The content of the repeating unit (b2) derived from (meth)acrylamide is 5 to 95 parts by mass when the total of the repeating units contained in the polymer (B) is 100 parts by mass. The lower limit of the content of the repeating unit (b2) is preferably 8 parts by mass, more preferably 10 parts by mass. The upper limit of the content of the repeating unit (b2) is preferably 90 parts by mass, more preferably 80 parts by mass. When the polymer (B) contains the repeating unit (b2) in the above range, the dispersibility of the active material and the filler is improved. In addition, the flexibility of the obtained active material layer becomes appropriate, and the adhesion between the current collector and the active material layer is improved. Furthermore, the bonding ability between the active materials containing a carbon material such as graphite and a silicon material can be increased, so that an active material layer having excellent flexibility and adhesion to the current collector can be obtained.

[0063] Examples of (meth)acrylamides include the same compounds as those exemplified in the description of the repeating unit (a5) above. Among these, it is preferable to use one or more types selected from acrylamide and methacrylamide.

[0064] 1.2.1.3. Other repeating units In addition to the repeating units (b1) and (b2), the polymer (B) may contain repeating units derived from other monomers copolymerizable therewith. Examples of such repeating units include repeating units (b3) derived from a conjugated diene compound (hereinafter also simply referred to as "repeating unit (b3)"), repeating units (b4) derived from an α,β-unsaturated nitrile compound (hereinafter also simply referred to as "repeating unit (b4)"), repeating units (b5) derived from an aromatic vinyl compound (hereinafter also simply referred to as "repeating unit (b5)"), repeating units (b6) derived from an unsaturated carboxylate ester (hereinafter also simply referred to as "repeating unit (b6)"), repeating units (b7) derived from a compound having a sulfonic acid group (hereinafter also simply referred to as "repeating unit (b7)"), and repeating units derived from a cationic monomer.

[0065] <Repeating unit (b3) derived from a conjugated diene compound> When the polymer (B) contains a repeating unit (b3) derived from a conjugated diene compound, the content of the repeating unit (b3) is preferably 0 to 10 parts by mass when the total of the repeating units contained in the polymer (B) is 100 parts by mass. The lower limit of the content of the repeating unit (b3) is preferably 0.5 parts by mass, more preferably 1 part by mass. The upper limit of the content of the repeating unit (b3) is preferably 9 parts by mass, more preferably 8 parts by mass. When the polymer (B) contains the repeating unit (b3) in the above range, the dispersibility of the active material and the filler is improved, and a uniform active material layer and a protective film can be prepared, so that the structural defects of the electrode plate are eliminated and good charge and discharge characteristics may be exhibited. In addition, the polymer (B) covering the surface of the active material can be given elasticity, and the polymer (B) can be stretched to improve adhesion, so that good charge and discharge durability characteristics may be exhibited.

[0066] The conjugated diene compound is not particularly limited, but may be the same compounds as those exemplified in the description of the repeating unit (a1) above. Among these, 1,3-butadiene is particularly preferred.

[0067] <Repeating unit (b4) derived from an α,β-unsaturated nitrile compound> When the polymer (B) contains a repeating unit (b4) derived from an α,β-unsaturated nitrile compound, the content of the repeating unit (b4) is preferably 0 to 10 parts by mass when the total of the repeating units contained in the polymer (B) is 100 parts by mass. The lower limit of the content of the repeating unit (b4) is preferably 0.5 parts by mass, more preferably 1 part by mass. The upper limit of the content of the repeating unit (b4) is preferably 9 parts by mass, more preferably 8 parts by mass. By containing the repeating unit (b4) in the above range in the polymer (B), it is possible to reduce the dissolution of the polymer (B) in the electrolyte solution, and the decrease in adhesion due to the electrolyte solution may be suppressed. In addition, the increase in internal resistance caused by the polymer component dissolved in the electricity storage device becoming an electric resistance component may be suppressed.

[0068] The α,β-unsaturated nitrile compound is not particularly limited, but may be the same compounds as those exemplified in the description of the repeating unit (a2) above. Among these, one or more selected from the group consisting of acrylonitrile and methacrylonitrile are preferred, and acrylonitrile is particularly preferred.

[0069] <Repeating unit (b5) derived from an aromatic vinyl compound> When the polymer (B) contains a repeating unit (b5) derived from an aromatic vinyl compound, the content of the repeating unit (b5) is preferably 0 to 10 parts by mass when the total of the repeating units contained in the polymer (B) is taken as 100 parts by mass. The lower limit of the content of the repeating unit (b5) is preferably 0.5 parts by mass, more preferably 1 part by mass. The upper limit of the content of the repeating unit (b5) is preferably 9 parts by mass, more preferably 8 parts by mass. When the polymer (B) contains the repeating unit (b5) in the above range, it has an appropriate binding strength with respect to graphite used as an active material, and an electricity storage device electrode having excellent flexibility and adhesion may be obtained.

[0070] The aromatic vinyl compound is not particularly limited, but may be the same compounds as those exemplified in the description of the repeating unit (a3). Among these, one or more selected from the group consisting of styrene and divinylbenzene are preferred, and styrene is particularly preferred.

[0071] <Repeating unit (b6) derived from unsaturated carboxylate> When the polymer (B) contains a repeating unit (b6) derived from an unsaturated carboxylate, the content of the repeating unit (b6) is preferably 0 to 30 parts by mass when the total of the repeating units contained in the polymer (B) is taken as 100 parts by mass. The lower limit of the content of the repeating unit (b6) is preferably 1 part by mass, more preferably 5 parts by mass. The upper limit of the content of the repeating unit (b6) is preferably 25 parts by mass, more preferably 20 parts by mass. When the polymer (B) contains the repeating unit (b6) in the above range, the affinity between the polymer (B) and the electrolyte is improved, and an increase in internal resistance due to the binder becoming an electric resistance component in the electricity storage device is suppressed, and a decrease in adhesion due to excessive absorption of the electrolyte may be prevented.

[0072] Among the unsaturated carboxylic acid esters, (meth)acrylic acid esters can be preferably used. Specific examples of (meth)acrylic acid esters are not particularly limited, but include the same compounds as those exemplified in the description of the repeating unit (a6) above.

[0073] <Repeating unit (b7) derived from a compound having a sulfonic acid group> When the polymer (B) contains a repeating unit (b7) derived from a compound having a sulfonic acid group, the content of the repeating unit (b7) is preferably 0 to 30 parts by mass when the total of the repeating units contained in the polymer (B) is 100 parts by mass. The lower limit of the content of the repeating unit (b7) is preferably 1 part by mass, more preferably 5 parts by mass. The upper limit of the content of the repeating unit (b7) is preferably 25 parts by mass, more preferably 20 parts by mass.

[0074] The compound having a sulfonic acid group is not particularly limited, but examples thereof include the same compounds as those exemplified in the description of the repeating unit (a7) above.

[0075] <Repeating units derived from cationic monomers> The polymer (B) may contain a repeating unit derived from a cationic monomer. The cationic monomer is not particularly limited, but is preferably at least one monomer selected from the group consisting of secondary amines (salts), tertiary amines (salts) and quaternary ammonium salts. The cationic monomer is not particularly limited, but may be the same compound as above.

[0076] 1.2.2. Physical properties of polymer (B) 1.2.2.1. Solubility in water The polymer (B) is preferably a water-soluble polymer. When the polymer (B) is a water-soluble polymer, the surface of the active material is easily coated with the polymer (B). As a result, the expansion of the active material during charging and discharging can be suppressed, and it is easy to obtain an electricity storage device that exhibits good charging and discharging durability characteristics. In the present invention, the "water-soluble polymer" refers to a polymer having a solubility in water of 1 g or more per 100 g of water at 25°C and 1 atmospheric pressure.

[0077] 1.2.2.2. Endothermic properties The polymer (B) more preferably has a temperature in the range of −20° C. to 150° C. when measured by differential scanning calorimetry (DSC) in accordance with JIS K7121. When the polymer (B) has only one endothermic peak in the DSC analysis and the peak temperature is in the above range, the polymer (B) preferably exhibits good adhesion and can impart better flexibility and adhesiveness to the active material layer.

[0078] 1.2.2.3.Viscosity When the viscosity of an aqueous solution of polymer (B) having a solid content concentration of 5% and a pH of 9 is measured at a temperature of 25° C. using a Brookfield viscometer, the viscosity is preferably 5 to 200,000 mPa·s / 30 rpm, more preferably 500 to 150,000 mPa·s / 30 rpm, and particularly preferably 1,000 to 100,000 mPa·s / 30 rpm. This viscosity can be measured in accordance with JIS Z 8803. As the Brookfield viscometer, for example, "RB-80L" or "TVB-10" manufactured by Toki Sangyo Co., Ltd. can be used.

[0079] 1.2.2.4. Weight average molecular weight (Mw) The weight average molecular weight (Mw) of the polymer (B) is preferably 5,000 or more and 2,000,000 or less, and more preferably 10,000 or more and 1,800,000 or less. 0 The weight average molecular weight of the polymer (B) is preferably 50,000 or more and 1,500,000 or less, and more preferably 50,000 or more and 1,500,000 or less. Mw When the molecular weight (Mw) is within the above range, the adhesion is good, and it is easy to obtain an electricity storage device having excellent charge / discharge characteristics. The weight average molecular weight of the polymer (B) can be measured, for example, by a GPC method under the following conditions. (Measurement conditions) Measuring equipment: Tosoh Corporation, GPC (model number: HLC-8220) Column: TSKgel guardcolum n P.W. XL (Tosoh Corporation), TSK-GEL G2500PW XL (Tosoh Corporation), TSK-GEL GMPW XL (Manufactured by Tosoh Corporation) Eluent: 0.1M NaNO3 aqueous solution Calibration curve: Standard polyethylene oxide Measurement method: Dissolve the polymer (B) in an eluent so that the solid content is 0.3 wt%, filter it, and then measure it.

[0080] 1.2.3. Method for synthesizing polymer (B) The synthesis method of the polymer (B) is not particularly limited, but solution polymerization carried out in a solvent mainly composed of water in the presence of a known chain transfer agent, polymerization initiator, etc. is preferred. A particularly preferred polymerization form is aqueous solution polymerization. Emulsion polymerization carried out in the presence of a known emulsifier (surfactant), chain transfer agent, polymerization initiator, etc. is also preferred.

[0081] The chain transfer agent used in solution polymerization of the polymer (B) is preferably a water-soluble chain transfer agent, and examples thereof include hypophosphites, phosphorous acids, thiols, secondary alcohols, and amines. In particular, thiols such as mercaptoacetic acid, 2-mercaptosuccinic acid, 3-mercaptopropionic acid, and 3-mercapto-1,2-propanediol are preferred. These water-soluble chain transfer agents may be used alone or in combination of two or more. The amount of the chain transfer agent used is preferably 5.0 parts by mass or less based on 100 parts by mass of the total mass of the monomers used in polymerization.

[0082] The polymerization initiator used when polymerizing the polymer (B) in solution is preferably a water-soluble radical initiator, and particularly preferably a persulfate such as lithium persulfate, potassium persulfate, sodium persulfate, or ammonium persulfate, or a water-soluble azo initiator such as 4,4'-azobis(4-cyanovaleric acid). The amount of the polymerization initiator used is preferably 0.1 to 5.0 parts by mass relative to 100 parts by mass of the total mass of the monomers used in the polymerization.

[0083] The polymerization temperature during synthesis of the polymer (B) is not particularly limited, but taking into consideration the production time and the conversion rate (reaction rate) of the monomers to the copolymer, the synthesis is preferably performed within a range of 30 to 95° C., more preferably 50 to 85° C. In addition, during polymerization, it is also possible to use a pH adjuster or a metal ion-sequestering agent such as EDTA or a salt thereof for the purpose of improving production stability.

[0084] In addition, the pH may be adjusted before or after polymerization with a general neutralizing agent such as ammonia, organic amine, potassium hydroxide, sodium hydroxide, or lithium hydroxide, and in this case, the pH is preferably adjusted to a range of 5 to 11. It is also possible to use a metal ion-sequestering agent such as EDTA or a salt thereof.

[0085] Furthermore, when the polymer (B) is emulsion polymerized, it can be, for example, an emulsion polymerization method carried out in the presence of a known emulsifier (surfactant), a chain transfer agent, a polymerization initiator, etc. Examples of known emulsifiers, chain transfer agents, and polymerization initiators include compounds described in Japanese Patent No. 5999399 and the like.

[0086] The solution polymerization or emulsion polymerization method for synthesizing the polymer (B) may be carried out by single-stage polymerization or by multi-stage polymerization of two or more stages.

[0087] When the synthesis of polymer (B) is carried out by single-stage polymerization, the mixture of the above-mentioned monomers can be subjected to emulsion polymerization in the presence of a suitable emulsifier, chain transfer agent, polymerization initiator, etc., preferably at 40 to 80°C, preferably for 1 to 18 hours.

[0088] When the synthesis of the polymer (B) is carried out by two-stage polymerization, it is preferable to set the polymerization in each stage as follows.

[0089] The proportion of the monomer used in the first-stage polymerization is preferably in the range of 40 to 100% by mass, more preferably in the range of 45 to 100% by mass, based on the total mass of the monomers (the sum of the mass of the monomers used in the first-stage polymerization and the mass of the monomers used in the second-stage polymerization). By carrying out the first-stage polymerization with such an amount of monomer, a polymer (B) having excellent dispersion stability and high binding strength can be obtained.

[0090] The type and ratio of the monomers used in the first-stage polymerization may be the same as or different from the type and ratio of the monomers used in the second-stage polymerization.

[0091] By controlling the total solids concentration in the solution polymerization or emulsion polymerization to 30% by mass or less, the polymerization reaction can be carried out in a state in which the dispersion stability of the resulting polymer is good. This total solids concentration is preferably 25% by mass or less, and more preferably 20% by mass or less.

[0092] Whether the synthesis of the polymer (B) is carried out by one-stage polymerization or two-stage polymerization, it is preferable to adjust the pH to about 3 to 11, preferably 4 to 10.5, more preferably 5 to 10, by adding a neutralizing agent to the polymerization mixture after the emulsion polymerization is completed. The neutralizing agent used here is not particularly limited, but examples thereof include metal hydroxides such as sodium hydroxide and potassium hydroxide; ammonia, etc. By setting the pH in the above range, the stability of the polymer (B) is improved. By concentrating the polymerization mixture after the neutralization treatment, the solid content concentration can be increased while maintaining the good stability of the polymer (B).

[0093] 1.3. Liquid medium (C) The composition for an electrical storage device according to this embodiment contains a liquid medium (C). The liquid medium (C) is preferably an aqueous medium containing water, and more preferably water. The aqueous medium can contain a non-aqueous medium other than water. Examples of such non-aqueous media include amide compounds, hydrocarbons, alcohols, ketones, esters, amine compounds, lactones, sulfoxides, and sulfone compounds, and one or more selected from these can be used. The composition for an electrical storage device according to this embodiment uses an aqueous medium as the liquid medium (C), thereby reducing the degree of adverse effects on the environment and increasing the safety for workers who handle the composition.

[0094] The content of the non-aqueous medium in the aqueous medium is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, and particularly preferably substantially free, per 100 parts by mass of the aqueous medium. Here, "substantially free" means that the non-aqueous medium is not intentionally added as a liquid medium, and may include a non-aqueous medium that is inevitably mixed in when preparing the composition for an electrical storage device.

[0095] 1.4. Other Additives The composition for an electrical storage device according to this embodiment may contain additives other than the above-mentioned components as necessary, such as a polymer other than the polymer particles (A) and the polymer (B), a preservative, a thickener, etc.

[0096] <Preservatives> The composition for an electrical storage device according to this embodiment may contain a preservative. By containing a preservative, it may be possible to suppress the proliferation of bacteria, mold, and the like and the generation of foreign matter when the composition for an electrical storage device is stored. Examples of the preservative include compounds described in Japanese Patent No. 5999399 and the like.

[0097] <Thickener> The composition for an electricity storage device according to this embodiment may contain a thickener. By containing a thickener, the coatability and the charge / discharge characteristics of the resulting electricity storage device may be further improved in some cases.

[0098] Examples of such thickeners include cellulose compounds such as carboxymethylcellulose, methylcellulose, and hydroxypropylcellulose; ammonium salts or alkali metal salts of the above cellulose compounds; polyvinyl alcohol (co)polymers such as polyvinyl alcohol, modified polyvinyl alcohol, and ethylene-vinyl alcohol copolymers; and water-soluble polymers such as saponified copolymers of unsaturated carboxylic acids such as (meth)acrylic acid, maleic acid, and fumaric acid with vinyl esters. Among these, particularly preferred thickeners are alkali metal salts of carboxymethylcellulose and alkali metal salts of poly(meth)acrylic acid.

[0099] Commercially available products of these thickeners include, for example, alkali metal salts of carboxymethylcellulose such as CMC1120, CMC1150, CMC2200, CMC2280, and CMC2450 (all manufactured by Daicel Corporation).

[0100] When the composition for electrical storage devices according to this embodiment contains a thickener, the content of the thickener is preferably 5 parts by mass or less, and more preferably 0.1 to 3 parts by mass, per 100 parts by mass of the total solid content of the composition for electrical storage devices.

[0101] 1.5. Properties of compositions for electricity storage devices 1.5.1. Mass ratio of polymer particles (A) to polymer (B) In the composition for an electric storage device according to the present embodiment, when the content of the polymer particles (A) is Ma parts by mass and the content of the polymer (B) is Mb parts by mass, the value of Mb / Ma is preferably 0.25 to 99. The lower limit of the value of Mb / Ma is preferably 0.25, more preferably 0.5, and particularly preferably 1. The upper limit of the value of Mb / Ma is preferably 99, more preferably 95, and particularly preferably 90. When the mass ratio of the polymer particles (A) to the polymer (B) in the composition for an electric storage device is within the above range, the polymer particles (A) exist like crosslinking points of the polymer (B), so that the polymer (B) tends to easily cover the active material around the polymer particles (A). Therefore, it is considered that an electric storage device electrode that not only has excellent adhesion but also exhibits very good charge / discharge durability characteristics that can suppress the expansion of the active material can be obtained.

[0102] 1.5.2.Viscosity When the composition for an electricity storage device according to the present embodiment, which has a solid content concentration of 5% and a pH of 9, is measured at a temperature of 25° C. using a Brookfield viscometer, the viscosity is preferably 5 to 150,000 mPa·s / 30 rpm, more preferably 500 to 130,000 mPa·s / 30 rpm, and particularly preferably 1,000 to 100,000 mPa·s / 30 rpm. When the viscosity of the composition for an electricity storage device is within the above range, excellent electrode applicability is obtained when a slurry for an electricity storage device is prepared. This viscosity can be measured in accordance with JIS Z 8803. As the Brookfield viscometer, for example, "RB-80L" or "TVB-10" manufactured by Toki Sangyo Co., Ltd. can be used.

[0103] pH The pH of the composition for an electricity storage device according to this embodiment is preferably 3 to 11, more preferably 4 to 10.5, and particularly preferably 5 to 10. When the pH of the composition for an electricity storage device is within this range, the occurrence of problems such as insufficient leveling and dripping during application of the slurry can be suppressed, making it easy to produce an electricity storage device electrode that combines good electrical properties and adhesion.

[0104] In this specification, "pH" refers to a physical property measured as follows. That is, it is a value measured at 25°C using a pH meter using a glass electrode calibrated with a neutral phosphate standard solution and a borate standard solution as pH standard solutions, in accordance with JIS Z8802:2011. Examples of such pH meters include "HM-7J" manufactured by DKK-TOA Corporation and "D-51" manufactured by HORIBA, LTD.

[0105] In a slurry prepared using a composition for an electrical storage device having a pH in the above range, the low pH corrodes the active material surface to an extent that does not deteriorate the charge / discharge characteristics, and the active material surface that has been exposed to the atmosphere and has become contaminated can be cleaned. As a result, it is believed that the obstruction of the absorption and release of lithium ions between the active material and the electrolyte in the obtained active material layer can be suppressed, and good charge / discharge characteristics can be exhibited.

[0106] It should be noted that the pH of the composition for an electricity storage device is not determined solely by the monomer composition, although it is not denied that the pH is affected by the monomer composition constituting the polymer particles (A) and the polymer (B). In other words, it is generally known that the pH of a composition for an electricity storage device changes depending on the polymerization conditions, etc., even if the monomer composition is the same, and the examples in this application merely show one example of this.

[0107] For example, even with the same monomer composition, the amount of carboxy groups derived from the unsaturated carboxylic acid exposed on the surface of the resulting polymer differs between the case where all the unsaturated carboxylic acid is charged into the polymerization reaction solution from the beginning and then other monomers are added sequentially, and the case where monomers other than the unsaturated carboxylic acid are charged into the polymerization reaction solution and the unsaturated carboxylic acid is added last. In this way, it is believed that the pH of the composition for electrical storage devices will differ significantly just by changing the order in which the monomers are added in the polymerization method.

[0108] 2. Slurry for electricity storage devices The slurry for an electric storage device according to one embodiment of the present invention contains the composition for an electric storage device described above. As described above, the composition for an electric storage device according to this embodiment can be used as a material for forming a protective film for suppressing a short circuit caused by dendrites that occur with charging and discharging, and can also be used as a material for producing an electrode for an electric storage device (active material layer) with improved bonding ability between active materials, adhesion ability between an active material and a current collector, and powder fall resistance. Therefore, the slurry for an electric storage device for forming a protective film (hereinafter also referred to as "slurry for a protective film") and the slurry for an electric storage device for forming an active material layer of an electrode for an electric storage device (hereinafter also referred to as "slurry for an electric storage device electrode") will be described separately.

[0109] 2.1.Slurry for protective film In this specification, the term "slurry for protective film" refers to a dispersion liquid used to form a protective film on the surface of an electrode or a separator, or both, by applying the dispersion liquid to the surface of an electrode or a separator, or both, and then drying the dispersion liquid. The slurry for protective film according to this embodiment may be composed only of the composition for an electric storage device described above, or may further contain an inorganic filler. Hereinafter, each component contained in the slurry for protective film according to this embodiment will be described in detail. Note that the composition for an electric storage device is as described above, so a description thereof will be omitted.

[0110] 2.1.1. Inorganic fillers The slurry for the protective film according to the present embodiment contains an inorganic filler, thereby improving the toughness of the protective film to be formed. As the inorganic filler, it is preferable to use at least one metal oxide particle selected from the group consisting of silica, titanium oxide (titania), aluminum oxide (alumina), zirconium oxide (zirconia), and magnesium oxide (magnesia). Among these, titanium oxide and aluminum oxide are preferable from the viewpoint of further improving the toughness of the protective film. Moreover, as the titanium oxide, rutile type titanium oxide is more preferable.

[0111] The average particle size of the inorganic filler is preferably 1 μm or less, and more preferably within the range of 0.1 to 0.8 μm. The average particle size of the inorganic filler is preferably larger than the average pore size of the separator, which is a porous membrane. This reduces damage to the separator and prevents the inorganic filler from clogging the micropores of the separator.

[0112] The protective film slurry according to this embodiment preferably contains 0.1 to 20 parts by mass, and more preferably 1 to 10 parts by mass, of the composition for an electrical storage device described above, calculated as solid content, per 100 parts by mass of inorganic filler. When the content ratio of the composition for an electrical storage device is within the above range, the balance between the toughness and lithium ion permeability of the formed protective film is good, and as a result, the resistance increase rate of the obtained electrical storage device can be further reduced.

[0113] 2.1.2. Liquid media The slurry for the protective film according to this embodiment may use the materials described in "1.3. Liquid medium (C)" in the composition for the electrical storage device as needed. The amount of the liquid medium added may be adjusted as needed to obtain an optimal slurry viscosity depending on the coating method, etc.

[0114] 2.1.3. Other additives The slurry for the protective film according to this embodiment can contain the materials described in "1.4. Other additives" in the composition for an electrical storage device described above in appropriate amounts as necessary.

[0115] 2.2. Slurry for electricity storage device electrodes In this specification, the term "slurry for an electricity storage device electrode" refers to a dispersion liquid used for applying the same to the surface of a current collector and then drying to form an active material layer on the current collector surface. The slurry for an electricity storage device electrode according to this embodiment contains the above-mentioned composition for an electricity storage device and an active material. The components contained in the slurry for an electricity storage device electrode according to this embodiment will be described below. Note that the composition for an electricity storage device is as described above, so a description thereof will be omitted.

[0116] 2.2.1.Active material Examples of active materials used in the slurry for the power storage device electrode according to this embodiment include carbon materials, silicon materials, oxides containing lithium atoms, lead compounds, tin compounds, arsenic compounds, antimony compounds, aluminum compounds, conductive polymers such as polyacene, A X B Y O Z (wherein A is an alkali metal or a transition metal, B is at least one selected from transition metals such as cobalt, nickel, aluminum, tin, and manganese, O is an oxygen atom, and X, Y, and Z are numbers within the ranges of 1.10>X>0.05, 4.00>Y>0.85, and 5.00>Z>1.5, respectively.) and other metal oxides. Specific examples of these include compounds described in Japanese Patent No. 5999399.

[0117] The electricity storage device electrode slurry according to this embodiment can be used when producing either a positive electrode or a negative electrode of an electricity storage device, and is preferably used for both a positive electrode and a negative electrode.

[0118] When lithium iron phosphate, a type of olivine-type lithium-containing phosphate compound, is used as the positive electrode active material, there is a problem that the charge / discharge characteristics are insufficient and adhesion is poor. Lithium iron phosphate has a fine primary particle size and is known to be a secondary aggregate, and one of the reasons is thought to be that the aggregates break down in the active material layer during repeated charge / discharge, causing separation of the active materials, leading to peeling from the current collector and disruption of the conductive network inside the active material layer.

[0119] However, the electricity storage device electrode produced using the electricity storage device electrode slurry according to this embodiment can exhibit good electrical properties without the above-mentioned problems even when lithium iron phosphate is used as the positive electrode active material. This is thought to be because the polymer particles (A) can firmly bind the lithium iron phosphate, and at the same time, the polymer (B) can maintain the lithium iron phosphate firmly bound state even during charging and discharging.

[0120] On the other hand, when preparing a negative electrode, among the active materials exemplified above, it is preferable to use one containing a silicon material. Since the amount of lithium absorbed per unit weight of a silicon material is larger than that of other active materials, the silicon material is contained as a negative electrode active material, so that the storage capacity of the power storage device can be increased, and as a result, the output and energy density of the power storage device can be increased.

[0121] In addition, the negative electrode active material is preferably a mixture of a silicon material and a carbon material.Since the volume change of the carbon material accompanying charge and discharge is smaller than that of the silicon material, by using the mixture of the silicon material and the carbon material as the negative electrode active material, the influence of the volume change of the silicon material can be mitigated, and the adhesion ability between the active material layer and the current collector can be further improved.

[0122] When silicon (Si) is used as an active material, while it has a high capacity, it undergoes a large volume change when it absorbs lithium. This causes the silicon material to pulverize due to repeated expansion and contraction, which can cause it to peel off from the current collector or separate from the active material itself, and the conductive network inside the active material layer can easily be disrupted. This causes the charge / discharge durability to deteriorate drastically in a short period of time.

[0123] However, the electricity storage device electrode produced using the electricity storage device electrode slurry according to this embodiment does not suffer from the above-mentioned problems and can exhibit good electrical properties even when a silicon material is used. This is believed to be because the polymer particles (A) can firmly bind the silicon material, and at the same time, the polymer (B) can maintain the silicon material firmly bound even when the silicon material expands in volume due to lithium occlusion.

[0124] The active material is preferably granular in shape. The average particle size of the active material is preferably 0.1 to 100 μm, and more preferably 1 to 20 μm. Here, the average particle size of the active material refers to the volume average particle size calculated from the particle size distribution measured using a particle size distribution measuring device that uses laser diffraction as the measurement principle. Examples of such laser diffraction type particle size distribution measuring devices include the HORIBA LA-300 series and the HORIBA LA-920 series (both manufactured by Horiba, Ltd.).

[0125] 2.2.2. Other additives In addition to the above-mentioned components, other components may be added to the slurry for an electricity storage device electrode according to this embodiment as necessary. Examples of such components include polymers other than the polymer particles (A) and the polymer (B), a conductivity imparting agent, a thickener, a liquid medium (excluding the portion carried over from the composition for an electricity storage device), a pH adjuster, a corrosion inhibitor, etc.

[0126] <Conductive agent> A conductivity imparting agent may be added to the slurry for an electricity storage device electrode according to this embodiment for the purposes of imparting electrical conductivity and buffering the volume change of the active material caused by the inflow and outflow of lithium ions.

[0127] Specific examples of the conductivity-imparting agent include carbon such as activated carbon, acetylene black, ketjen black, furnace black, graphite, carbon fiber, and fullerene. Among these, acetylene black and furnace black can be preferably used. The content of the conductivity-imparting agent is preferably 20 parts by mass or less, more preferably 1 to 15 parts by mass, and particularly preferably 2 to 10 parts by mass, relative to 100 parts by mass of the active material.

[0128] <Thickener> A thickener may be added to the slurry for an electricity storage device electrode according to this embodiment in order to improve the coating property. Specific examples of the thickener include the compounds described in "1.4. Other Additives". The content of the thickener is preferably 0.1 to 10 parts by mass, more preferably 0.5 to 5 parts by mass, relative to 100 parts by mass of the active material.

[0129] <Liquid medium> The slurry for an electricity storage device electrode according to this embodiment contains the above-mentioned composition for an electricity storage device, and therefore contains the liquid medium (C) contained in the composition for an electricity storage device. In addition to the liquid medium (C) carried over from the composition for an electricity storage device, a liquid medium other than the liquid medium (C) may be added to the slurry for an electricity storage device electrode according to this embodiment, if necessary.

[0130] The liquid medium that can be added to the slurry for an electricity storage device electrode in this embodiment may be the same as or different from the liquid medium (C) contained in the composition for an electricity storage device, but it is preferable to select and use one from the liquid media exemplified in "1.3. Liquid medium (C)".

[0131] In the slurry for a power storage device electrode according to this embodiment, the usage ratio of the liquid medium (including the carry-in from the composition for a power storage device) is preferably such that the solid content concentration in the slurry (which refers to the ratio of the total mass of components other than the liquid medium in the slurry to the total mass of the slurry. The same applies hereinafter) is 30 to 70% by mass, and more preferably 40 to 60% by mass.

[0132] <pH adjuster / corrosion inhibitor> In the slurry for a power storage device electrode according to this embodiment, a pH adjuster or a corrosion inhibitor may be added for the purpose of suppressing the corrosion of the current collector according to the type of the active material.

[0133] Examples of the pH adjuster include hydrochloric acid, phosphoric acid, sulfuric acid, acetic acid, formic acid, ammonium phosphate, ammonium sulfate, ammonium acetate, ammonium formate, ammonium chloride, sodium hydroxide, potassium hydroxide, etc. Among these, sulfuric acid, ammonium sulfate, sodium hydroxide, and potassium hydroxide are preferred. Also, it can be selected and used from among the neutralizing agents described in the synthesis method of the polymer particles (A) or the polymer (B).

[0134] Examples of the corrosion inhibitor include ammonium metavanadate, sodium metavanadate, potassium metavanadate, ammonium metatungstate, sodium metatungstate, potassium metatungstate, ammonium paratungstate, sodium paratungstate, potassium paratungstate, ammonium molybdate, sodium molybdate, potassium molybdate, etc. Among these, ammonium paratungstate, ammonium metavanadate, sodium metavanadate, potassium metavanadate, and ammonium molybdate are preferred.

[0135] 2.2.3. Method for manufacturing the slurry for a power storage device electrode The slurry for an electric storage device electrode according to this embodiment may be produced by any method as long as it contains the above-mentioned composition for an electric storage device and an active material, but can be produced, for example, by the method described in Japanese Patent No. 5999399.

[0136] 3.Electricity storage device electrodes The electricity storage device electrode according to this embodiment includes a current collector and an active material layer formed by applying and drying the above-mentioned slurry for an electricity storage device electrode on the surface of the current collector. Such an electricity storage device electrode can be manufactured by applying the above-mentioned slurry for an electricity storage device electrode to the surface of a current collector such as a metal foil to form a coating film, and then drying the coating film to form an active material layer. The electricity storage device electrode manufactured in this manner is formed by binding an active material layer containing the above-mentioned polymer particles (A), polymer (B), and active material, and further optional components added as necessary, on a current collector, and therefore has excellent adhesion and exhibits good charge / discharge durability characteristics.

[0137] The current collector is not particularly limited as long as it is made of a conductive material, and examples thereof include the current collectors described in Japanese Patent No. 5999399 and the like.

[0138] There are no particular limitations on the method for applying the slurry for an electricity storage device electrode to a current collector, and the slurry can be applied by the method described in Japanese Patent No. 5,999,399 or the like.

[0139] In the electricity storage device electrode according to this embodiment, when a silicon material is used as the active material, the content of elemental silicon in 100 parts by mass of the active material layer is preferably 2 to 40 parts by mass, more preferably 2 to 30 parts by mass, and particularly preferably 3 to 20 parts by mass. When the content of elemental silicon in the active material layer is within the above range, the electricity storage capacity of the electricity storage device produced using it is improved, and an active material layer with a uniform distribution of elemental silicon can be obtained.

[0140] In the present invention, the content of silicon element in the active material layer can be measured by the method described in Japanese Patent No. 5,999,399, for example.

[0141] 4. Energy storage devices The power storage device according to this embodiment includes the above-mentioned power storage device electrode, further contains an electrolyte, and can be manufactured by a conventional method using components such as a separator. A specific manufacturing method includes, for example, stacking a negative electrode and a positive electrode with a separator interposed therebetween, and storing the stack in a battery container by rolling or folding the stack according to the battery shape, and injecting an electrolyte into the battery container and sealing the container. The shape of the battery can be any appropriate shape, such as a coin type, a cylindrical type, a square type, or a laminate type.

[0142] The electrolyte may be liquid or gel, and may be selected from among known electrolytes used in power storage devices that effectively exhibit the function of a battery depending on the type of active material. The electrolyte may be a solution in which an electrolyte is dissolved in a suitable solvent. Examples of such electrolytes and solvents include compounds described in Japanese Patent No. 5999399.

[0143] The above-mentioned electric storage device can be applied to lithium ion secondary batteries, electric double layer capacitors, lithium ion capacitors, etc., which require discharge at a high current density. Among these, lithium ion secondary batteries are particularly preferred. In the electric storage device electrode and electric storage device according to this embodiment, members other than the composition for electric storage devices can be known members for lithium ion secondary batteries, electric double layer capacitors, and lithium ion capacitors.

[0144] 5. Working Example The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the examples and comparative examples, "parts" and "%" are by mass unless otherwise specified.

[0145] 5.1. Synthesis of polymer (A) <Synthesis Example of Polymer (A1)> In a reactor, 400 parts by mass of water, 45 parts by mass of 1,3-butadiene, 25 parts by mass of acrylonitrile, 5 parts by mass of styrene, 5 parts by mass of acrylic acid, 15 parts by mass of methacrylic acid, and 5 parts by mass of acrylamide were charged, and 0.1 parts by mass of tert-dodecyl mercaptan as a chain transfer agent, 1 part by mass of sodium alkyl diphenyl ether disulfonate as an emulsifier, and 0.2 parts by mass of potassium persulfate as a polymerization initiator were charged, and the mixture was polymerized at 70°C for 24 hours while stirring. The reaction was terminated at a polymerization conversion rate of 98%. Unreacted monomers were removed from the dispersion of polymer (A1) thus obtained, and after concentration, a 10% aqueous sodium hydroxide solution and water were added to obtain a polymer dispersion containing 5% by mass of polymer (A1) particles with a pH of 9.0.

[0146] <Synthesis Examples of Polymer (A2) to Polymer (A12)> Polymers (A2) to (A12) were synthesized in the same manner as in the synthesis example of polymer (A1) above, except that the types and content ratios of the monomers used were changed as shown in Table 1 below, and each polymer dispersion was obtained.

[0147] <Measurement of number average particle size> The particle size distribution of each of the polymers (A1) to (A12) obtained above was measured using a particle size distribution measuring device (manufactured by Otsuka Electronics Co., Ltd., model "FPAR-1000") that uses dynamic light scattering as its measurement principle, and the number average particle size was calculated from the particle size distribution. The measurement conditions were as follows. The measurement results are also shown in Table 1 below. (Measurement conditions) ·Dispersion medium: water ·Measurement temperature: 25℃ Dilution ratio: 0.1wt% ·Scattering angle: 160° Light source laser wavelength: 632.8nm

[0148] <Viscosity measurement> The viscosity of the polymer dispersion obtained above at a temperature of 25°C was measured in accordance with JIS Z 8803. The viscometer used was a B-type viscometer (manufactured by Toki Sangyo Co., Ltd., model "RB-80L"). The measurement results are also shown in Table 1 below.

[0149] <Measurement of Weight-Average Molecular Weight of THF-Soluble Component> 10 mg of the polymer dispersion obtained above was mixed with 5 mL of THF, allowed to stand at 25 °C for 16 hours, and then passed through a 0.45-μm membrane filter to obtain a measurement sample. Next, under the following measurement conditions, using the obtained measurement sample, the weight-average molecular weight (Mw) of the THF-soluble component was determined by polystyrene conversion (RI detection) using gel permeation chromatography with the following columns. The measurement results are shown in Table 1 below. (Measurement Conditions) · Temperature: 35 °C · Solvent: THF · Flow rate: 1.0 mL / min · Concentration: 0.2 wt% · Injection volume of measurement sample: 100 μL (Columns) · Two columns of "GPC TSKgel α-2500" (30 cm) manufactured by Tosoh Corporation were used. (Measurement was carried out under the condition that the primary correlation coefficient between Log 10 (Mw) and elution time was 0.98 or more.)

[0150]

Table 1

[0151] The abbreviations of each component in Table 1 above represent the following compounds respectively. Also, the numerical values of each component in Table 1 above represent parts by mass. <Conjugated Diene Compound> · BD: 1,3-Butadiene <α,β-Unsaturated Nitrile Compound> · AN: Acrylonitrile <Aromatic Vinyl Compound> · ST: Styrene · DVB: Divinylbenzene <Unsaturated Carboxylic Acid> · TA: Itaconic Acid · AA: Acrylic Acid · MAA: Methacrylic Acid <(Meth)acrylamide> ·AAM: Acrylamide ·MAM: Methacrylamide <Unsaturated carboxylic acid ester> ·MMA: Methyl methacrylate ·BA: n-Butyl acrylate ·2EHA: 2-Ethylhexyl acrylate ·CHMA: Cyclohexyl methacrylate ·EDMA: Ethylene glycol dimethacrylate ·HEMA: 2-Hydroxyethyl methacrylate ·HEA: 2-Hydroxyethyl acrylate <Compound having a sulfonic acid group> ·NASS: Sodium styrene sulfonate

[0152] 5.2. Synthesis of Polymer (B) <Synthesis example of Polymer (B1)> Into a reactor, 900 parts by mass of water, 25 parts by mass of acrylic acid, and 75 parts by mass of acrylamide were charged, 0.2 parts by mass of potassium persulfate was charged as a polymerization initiator, and polymerization was carried out at 70 °C for 10 hours. The reaction was terminated at a polymerization conversion rate of 98%. To the thus obtained Polymer (B1), an aqueous solution of 10% sodium hydroxide and water were added to obtain a Polymer (B1) - containing solution having a solid content concentration of 5% and a pH of 9.

[0153] <Synthesis examples of Polymers (B2) to (B12)> Polymers (B2) to (B12) were synthesized in the same manner as in the synthesis example of the above Polymer (B1), except that the types and content ratios of the monomers used were changed as shown in Table 2 below, and each Polymer - containing solution was obtained.

[0154] <Solubility in water> At 25 °C and 1 atm, it was visually observed whether 1 g of each of the above - obtained Polymers (B1) to (B12) was completely dissolved in 100 g of water. The results are shown together with Table 2 below. In the table, the case of complete dissolution was described as "A", and the case where undissolved residue was present was described as "B".

[0155] <pH measurement> When the pH of each of the polymer-containing liquids obtained above was measured at 25° C. using a pH meter (manufactured by Horiba, Ltd.), it was confirmed that the pH of each of the polymer-containing liquids was 9.0.

[0156] <Viscosity measurement> The viscosity of each of the polymer-containing liquids obtained above at a temperature of 25° C. was measured in accordance with JIS Z 8803. The viscometer used was a B-type viscometer (manufactured by Toki Sangyo Co., Ltd., model “RB-80L”). The measurement results are shown in Table 2 below.

[0157] <Weight average molecular weight (Mw)> The weight average molecular weight of the polymer (B) obtained above was measured by GPC under the following conditions. The measurement results are shown in Table 2 below. (Measurement conditions) Measuring equipment: Tosoh Corporation, GPC (model number: HLC-8220) Column: TSKgel guardcolum PW XL (Tosoh Corporation), TSK-GEL G2500PW XL (Tosoh Corporation), TSK-GEL GMPW XL (Manufactured by Tosoh Corporation) Eluent: 0.1M NaNO3 aqueous solution Calibration curve: Standard polyethylene oxide Measurement method: Dissolve the polymer (B) in an eluent so that the solid content is 0.3 wt%, filter it, and then measure it.

[0158] [Table 2]

[0159] The abbreviations of each component in Table 2 above are the same as those in Table 1 above. The numerical values ​​of each component in Table 2 above indicate parts by mass.

[0160] 5.3. Example 1 5.3.1. Preparation and Evaluation of Compositions for Electric Storage Devices (1) Preparation of composition for electrical storage device The polymer dispersion liquid containing polymer (A1) and the polymer-containing liquid containing polymer (B1) obtained above were added in amounts corresponding to 10 parts by mass of polymer (A1) and 90 parts by mass of polymer (B1), respectively, and stirred at 60 rpm for 1 hour, thereby obtaining a composition for electrical storage devices used in Example 1.

[0161] (2)pH measurement The pH of the composition for an electricity storage device obtained above was measured at 25° C. using a pH meter (manufactured by Horiba, Ltd.), and it was confirmed that the pH was 9.0.

[0162] (3) Viscosity measurement The viscosity of the composition for use in an electricity storage device obtained above at a temperature of 25° C. was measured in accordance with JIS Z 8803. The viscometer used was a B-type viscometer (manufactured by Toki Sangyo Co., Ltd., model "RB-80L"). The measurement results are also shown in Table 3 below.

[0163] 5.3.2. Preparation of Slurry for Electricity Storage Device Electrodes (1) Synthesis of silicon material (active material) A mixture of crushed silicon dioxide powder (average particle size: 10 μm) and carbon powder (average particle size: 35 μm) was heat-treated for 10 hours in an electric furnace with the temperature adjusted to the range of 1100 to 1600 °C under a nitrogen gas flow (0.5 NL / min) to obtain a mixture of silicon dioxide powder with the composition formula SiO xA silicon oxide powder (average particle size 8 μm) represented by (x=0.5-1.1) was obtained. 300 g of this silicon oxide powder was charged into a batch-type heating furnace, and while maintaining a reduced pressure of 100 Pa absolute pressure by a vacuum pump, the temperature was raised from room temperature (25 ° C) to 1100 ° C at a heating rate of 300 ° C / h. Next, while maintaining the pressure in the heating furnace at 2000 Pa, methane gas was introduced at a flow rate of 0.5 NL / min, and a heat treatment (graphite coating treatment) was performed at 1100 ° C for 5 hours. After the graphite coating treatment, the powder was cooled to room temperature at a temperature drop rate of 50 ° C / h to obtain about 330 g of graphite-coated silicon oxide powder. This graphite-coated silicon oxide was a conductive powder (active material) in which the surface of silicon oxide was coated with graphite, with an average particle size of 10.5 μm. The proportion of the graphite coating was 2 mass% when the entirety of the obtained graphite-coated silicon oxide was taken as 100 mass%.

[0164] (2) Preparation of slurry for power storage device electrodes A two-shaft planetary mixer (manufactured by Primix Corporation, product name "TK Hivismix 2P-03") was mixed with 0.4 parts by mass of polymer (A1), 3.6 parts by mass of polymer (B1) (solid content equivalent, added as the obtained composition for an electricity storage device), 76 parts by mass (solid content equivalent) of artificial graphite (manufactured by Hitachi Chemical Co., Ltd., product name "MAG") which is a highly crystalline graphite as a negative electrode active material, and the graphite obtained above. Coating 19 parts by mass (solid content equivalent) of silicon oxide powder and 1 part by mass of carbon (acetylene black, manufactured by Denka Co., Ltd.) as a conductivity imparting agent were added, and the mixture was stirred at 60 rpm for 1 hour to obtain a paste. Water was added to the obtained paste to adjust the solid content concentration to 48% by mass, and then the mixture was stirred at 200 rpm for 2 minutes, at 1800 rpm for 5 minutes, and further under reduced pressure (approximately 2.5×10 4 The mixture was stirred and mixed at 1,800 rpm for 1.5 minutes at 1000 Pa to prepare a slurry for an electricity storage device electrode (C / Si=80 / 20) containing 20 mass % of Si in the negative electrode active material.

[0165] 5.3.3. Manufacturing and evaluation of energy storage devices (1) Manufacturing of electrodes (negative electrodes) for power storage devices The slurry for an electric storage device electrode (C / Si=80 / 20) obtained above was uniformly applied by a doctor blade method onto the surface of a current collector made of copper foil with a thickness of 20 μm so that the film thickness after drying would be 80 μm, and the coating was dried at 60° C. for 10 minutes and then at 120° C. for 10 minutes. After that, the density of the active material layer was 1.5 g / cm 3 The mixture was pressed by a roll press machine so as to obtain an electricity storage device electrode (negative electrode).

[0166] (2) Evaluation of adhesion strength of negative electrode coating layer A knife was used to make 10 incisions in each direction at 2 mm intervals on the surface of the electrode sheet obtained above, from the active material layer to a depth reaching the current collector, creating a grid pattern. An 18 mm wide adhesive tape (manufactured by Nichiban Co., Ltd., product name "Cellotape" (registered trademark), as specified in JIS Z1522) was attached to the incisions and immediately peeled off, and the degree of loss of the active material was evaluated by visual inspection. The evaluation criteria were as follows. The evaluation results are shown in Table 3 below. (Evaluation Criteria) 5 points: No active material layers fell off. 4 points: 1 to 5 pieces of the active material layer are missing. 3 points: 6 to 20 pieces of the active material layer have fallen off. 2 points: 21 to 40 pieces of the active material layer fell off. 1 point: 41 or more pieces of the active material layer are missing.

[0167] (3) Manufacturing the counter electrode (positive electrode) Into a two-shaft planetary mixer (manufactured by Primix Corporation, product name "TK Hivismix 2P-03"), 4.0 parts by mass (solid content equivalent) of an electrochemical device electrode binder (manufactured by Kureha Corporation, product name "KF Polymer #1120", hereinafter abbreviated as "PVDF"), 3.0 parts by mass of a conductive assistant (manufactured by Denki Kagaku Kogyo Co., Ltd., product name "Denka Black 50% Pressed Product"), 100 parts by mass (solid content equivalent) of LiCoO2 (manufactured by Hayashi Kasei Co., Ltd.) with an average particle diameter of 5 μm as a positive electrode active material, and 36 parts by mass of N-methylpyrrolidone (NMP) were added and stirred at 60 rpm for 2 hours. After adding NMP to the obtained paste to adjust the solid content concentration to 65 mass%, a stirring and defoaming machine (manufactured by Thinky Corporation, product name "Awatori Rentaro") was used to stir the mixture at 200 rpm for 2 minutes, at 1,800 rpm for 5 minutes, and further under reduced pressure (approximately 2.5 × 10 4 The slurry for the positive electrode was prepared by stirring and mixing at 1,800 rpm for 1.5 minutes at 1000 rpm (Pa). The slurry for the positive electrode was uniformly applied to the surface of a current collector made of aluminum foil by a doctor blade method so that the film thickness after solvent removal would be 80 μm, and the solvent was removed by heating at 120° C. for 20 minutes. Thereafter, the density of the active material layer was 3.0 g / cm 3 A counter electrode (positive electrode) was obtained by pressing the mixture with a roll press machine so that the resultant mixture was as follows:

[0168] (4) Assembly of lithium-ion battery cells In a glove box substituted with Ar gas so that the dew point was -80°C or less, the negative electrode produced above was punched out to a diameter of 15.95 mm and placed on a two-electrode coin cell (manufactured by Hosen Co., Ltd., product name "HS Flat Cell"). Next, a separator made of a polypropylene porous film punched out to a diameter of 24 mm (manufactured by Celgard Co., Ltd., product name "Celgard #2400") was placed on the cell, and 500 μL of electrolyte was poured to prevent air from entering. The positive electrode produced above was punched out to a diameter of 16.16 mm and placed on the cell, and the exterior body of the two-electrode coin cell was sealed with screws to assemble a lithium-ion battery cell (electricity storage device). The electrolyte used here was a solution in which LiPF6 was dissolved at a concentration of 1 mol / L in a solvent of ethylene carbonate / ethyl methyl carbonate = 1 / 1 (mass ratio).

[0169] (5) Evaluation of charge / discharge cycle characteristics The energy storage device manufactured above was charged at a constant current (1.0C) in a thermostatic chamber adjusted to 25°C, and when the voltage reached 4.2V, charging was continued at a constant voltage (4.2V), and charging was completed (cut-off) when the current value reached 0.01C. Discharging was then started at a constant current (1.0C), and discharging was completed (cut-off) when the voltage reached 3.0V, and the discharge capacity of the first cycle was calculated. In this manner, charging and discharging were repeated 100 times. The capacity retention rate was calculated using the following formula and evaluated according to the following criteria. The evaluation results are shown in Table 3 below. Capacity retention rate (%) = (discharge capacity at 100th cycle) / (discharge capacity at 1st cycle) (Evaluation Criteria) 5 points: Capacity retention is 95% or more. 4 points: Capacity retention is between 90% and 95%. 3 points: Capacity retention is between 85% and 90%. 2 points: Capacity retention is between 80% and 85%. 1 point: Capacity retention is between 75% and 80%. 0 points: Less than 75% capacity retention.

[0170] In the measurement conditions, "1C" refers to the current value at which a cell with a certain capacity is discharged at a constant current and the discharge is completed in 1 hour. For example, "0.1C" refers to the current value at which the discharge is completed in 10 hours, and "10C" refers to the current value at which the discharge is completed in 0.1 hour.

[0171] 5.4. Examples 2 to 9 and Comparative Examples 1 to 8 A composition for an electricity storage device was obtained in the same manner as in Example 1, except that in "5.3.1. Preparation and evaluation of composition for electricity storage device (1) Preparation of composition for electricity storage device" in Example 1 above, the types and content ratios of polymer (A) and polymer (B) were changed to those shown in Table 3 or Table 4 below. Furthermore, a slurry for an electricity storage device electrode was prepared in the same manner as in Example 1, except that the composition for an electricity storage device prepared in this manner was used, and an electricity storage device electrode and an electricity storage device were fabricated and evaluated in the same manner as in Example 1 above.

[0172] 5.5.Evaluation Results Tables 3 and 4 below show the compositions for electricity storage devices used in Examples 1 to 9 and Comparative Examples 1 to 8, as well as the evaluation results.

[0173] [Table 3]

[0174] [Table 4]

[0175] As is clear from Table 3, the negative electrodes produced using the compositions for electricity storage devices according to the present invention shown in Examples 1 to 9 all had excellent adhesion. Furthermore, the electricity storage devices including the negative electrodes had excellent capacity retention after 100 cycles even when using an active material containing a silicon material.

[0176] On the other hand, as is clear from Table 4, the negative electrodes prepared using the compositions for electricity storage devices shown in Comparative Examples 1 to 8 tended to have inferior adhesion compared to those of the Examples. Furthermore, the electricity storage devices including these negative electrodes also tended to have a lower capacity retention rate after 100 cycles.

[0177] 5.6. Examples 10 to 13 <Example 10> In the same manner as in Example 7, polymer dispersion liquid (A7) and polymer-containing liquid (B7) were added in amounts equivalent to 25 parts by mass of polymer (A7) and 75 parts by mass of polymer (B7), respectively, and stirred at 60 rpm for 1 hour to obtain a composition for storage batteries used in Example 10. Next, into a two-shaft planetary mixer (manufactured by Primix Corporation, product name "TK Hivismix 2P-03") were added 1 part by mass (solid content equivalent, added as an aqueous solution with a concentration of 2% by mass) of a thickener (product name "CMC2200", manufactured by Daicel Corporation) as a pre-addition component, 3 parts by mass (solid content equivalent) of the composition for the energy storage device described above, 76 parts by mass (solid content equivalent) of artificial graphite (manufactured by Hitachi Chemical Co., Ltd., product name "MAG") which is highly crystalline graphite as a negative electrode active material, 19 parts by mass (solid content equivalent) of the graphite-coated silicon oxide powder obtained above, and 1 part by mass of carbon (manufactured by Denka Company, Ltd., acetylene black) as a conductivity imparting agent, and the mixture was stirred at 60 rpm for 1 hour to obtain a paste. Water was added to the obtained paste to adjust the solid concentration to 48% by mass, and then the mixture was stirred at 200 rpm for 2 minutes, at 1800 rpm for 5 minutes, and then further stirred under reduced pressure (approximately 2.5 × 10 4 The mixture was stirred and mixed at 1,800 rpm for 1.5 minutes at 1000 Pa to prepare a slurry for an electricity storage device electrode (C / Si=80 / 20) containing 20 mass % of Si in the negative electrode active material.

[0178] An electricity storage device electrode and an electricity storage device were produced in the same manner as in Example 1 above, except that the above-obtained electricity storage device electrode slurry was used, and evaluated in the same manner as in Example 1 above.

[0179] <Example 11> An electricity storage device electrode and an electricity storage device were each produced in the same manner as in Example 10 above, except that the thickener in the electricity storage device electrode slurry obtained in Example 10 above was changed to 3 parts by mass, and evaluated in the same manner as in Example 1 above.

[0180] <Examples 12 and 13> In the slurries for electricity storage device electrodes obtained in Examples 10 and 11 above, except that compositions for electricity storage devices were used to which only 5 parts by mass of the polymer dispersion liquid (A3) and 95 parts by mass of the polymer-containing liquid (B9) similar to those in Example 9 were added, were used, electricity storage device electrodes and electricity storage devices were prepared in the same manner as in Examples 10 and 11 above, and evaluated in the same manner as in Example 1 above.

[0181] 5.7.Evaluation Results Table 5 below shows the compositions for electricity storage devices used in Examples 10 to 13 and the evaluation results.

[0182] [Table 5]

[0183] As is clear from Table 5, the electricity storage devices according to the present invention shown in Examples 10 to 13 Using group It was found that the slurry for energy storage device electrodes prepared using this composition, even when used in combination with the thickener CMC, was able to effectively bind active materials that undergo large volume changes during charging and discharging, and also maintained good adhesion between the active material layer and the current collector.

[0184] The present invention is not limited to the above-described embodiments, and various modifications are possible. The present invention includes configurations that are substantially the same as those described in the embodiments (for example, configurations with the same functions, methods, and results, or configurations with the same purpose and effect). The present invention also includes configurations in which non-essential parts of the configurations described in the above-described embodiments are replaced with other configurations. Furthermore, the present invention also includes configurations that have the same effects as the configurations described in the above-described embodiments, or that can achieve the same purpose. Furthermore, the present invention also includes configurations in which publicly known technology is added to the configurations described in the above-described embodiments.

Claims

1. Contains polymer particles (A), a polymer (B), and a liquid medium (C), When the total amount of repeating units contained in the polymer particles (A) is 100 parts by mass, the polymer particles (A) 20 to 65 parts by mass of a repeating unit (a1) derived from a conjugated diene compound; and 1 to 40 parts by mass of a repeating unit (a2) derived from an α,β-unsaturated nitrile compound, When the total amount of repeating units contained in the polymer (B) is 100 parts by mass, the polymer (B) 5 to 95 parts by mass of a repeating unit (b1) derived from an unsaturated carboxylic acid; and 5 to 95 parts by mass of a repeating unit (b2) derived from (meth)acrylamide.

2. 2. The composition for an electrical storage device according to claim 1, wherein a value of Mb / Ma is 0.25 to 99, where Ma is the content of the polymer particles (A) and Mb is the content of the polymer (B).

3. The composition for an electrical storage device according to claim 1 or 2, wherein the polymer particles (A) have a number average particle size of 50 nm or more and 500 nm or less.

4. The composition for an electrical storage device according to claim 1 , wherein the liquid medium (C) is water.

5. A slurry for an electrode of an electricity storage device, comprising the composition for an electricity storage device according to claim 1 and an active material.

6. The slurry for an electric storage device electrode according to claim 5 , which contains a silicon material as the active material.

7. The slurry for an electricity storage device electrode according to claim 5 or 6, further comprising a thickener.

8. 8. An electricity storage device electrode comprising: a current collector; and an active material layer formed by applying the slurry for an electricity storage device electrode according to claim 5 onto a surface of the current collector and drying the slurry.

9. An electricity storage device comprising the electricity storage device electrode according to claim 8 .

Citation Information

Patent Citations

  • Locking device of tape reel

    JP1983062878A

  • Electrode material for lithium secondary battery, electrode structural body with the electrode material, secondary battery with the electrode structure, manufacturing method of the electrode material, manufacturing method of the electrode structural body, and manufacturing method of the secondary battery

    JP2004185810A

  • Method for manufacturing nonaqueous electrolytic solution battery

    JP2007294323A

  • Binder composition, slurry for battery electrode, electrode, and lithium secondary battery

    JP2010003703A

  • Binder for nonaqueous electrolyte secondary battery electrode

    JP2010205722A